Application of "Fashion Design Process” in Developing Contemporary Fashion-Collection Based on Batik Purbalingga - Tasyrif Adnan; Farahiyah Inarah Putri (Jurnal Sosial Teknologi, 2026)
Background:Fashion designers in Purbalingga face challenges due to limited knowledge of a systematic fashion collection development process. The existing creative process often relies on self-taught skills or the transfer of abilities from other artistic disciplines, which highlights the need for a structured framework to guide designers in developing fashion collections. Objective:This study aims to introduce the Fashion Design Process (FDP) framework to local designers and evaluate its effectiveness in supporting their creative process and fashion collection development. Methods:The research was conducted in several stages, including the introduction of the FDP framework, assignments and mentorship, as well as monitoring and evaluation. The framework was introduced through classroom sessions involving portfolio analysis, recommendations, and examples of application. The effectiveness of the program was assessed through direct interviews with participants after the program. Results:The results show that all participants, regardless of their educational background, were able to complete the assignments according to the stages of the Fashion Design Process. The quality of their work also improved, as reflected in the jury’s evaluation during the runway presentation. However, the research stage was identified as the most challenging and time-consuming part of the process. Conclusion:The Fashion Design Process (FDP) framework proved effective in helping local designers structure their creative process and improve the quality of their design work. Nevertheless, the research stage requires further evaluation and improvement in future programs.